From page to screen: exploring Malaysian teachers' perspectives on the feasibility of a mobile reading module - Umi Zafirah Othman; Noraini Said (Penerbit UMS, 2024)
Among the significant challenges several Malaysian teachers face, especially those teaching in primary school, is the need for more resources to teach reading comprehension. The implementation of mobile technologies provides favourable opportunities to facilitate teachers’ teaching competencies in teaching reading comprehension instructions. Nevertheless, the successful implementation of the mobile reading module depends on the perceptions and contributions of teachers. This study investigates the viewpoints of Malaysian primary school teachers regarding the needs and development of a mobile reading module. A survey with open-ended questions was sent to nine Year 5 teachers in Sabah, Malaysia, to collect their perspectives. All the teachers who participated in the activity provided constructive opinions regarding a mobile reading module, highlighting the potential advantages of using the mobile reading module to facilitate teaching instructions. The findings offer significant viewpoints from Malaysian primary school teachers regarding developing and implementing mobile reading initiatives. These findings may influence the development of mobile reading materials that are both relevant to the context and coordinated with teachers to improve teaching comprehension skills among teachers in Malaysia.